A tecnologia e a informação na construção de valores de responsabilidade social - Dantas, Willy de Macedo [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
In the last decades the technology has been incorporated to the way reality to reconfigure the current scene all, bringing I obtain deep transformations that excessively impact in all the fields of the human knowledge and in the social behavior. In the information the impacts have been right-handers, leading in consideration the concurrence of the technology process to the informational explosion and its applicability in the organizational environment. In this direction, it appears as problem the impact that the allied technology to the information has on the construction of social values of the culture of an organization. This work searchs to understand the way as the technology and the information comes working in its dissemination and, in this way, to construct the values that are make a speeched for the socially responsible organizations, ahead of the reality of the new context of the revolution of the TIC's -Technologies of the Information and Communication. The work follows as north axles of quarrel and study, being: technology -information -organizational culture and social responsibility. In intention to organize the search for this knowledge, they are made use of the comparative method to form the scene of the socially responsible organizations, using itself of two instruments of collection of data, the interview and the questionnaire. Through the collected data, understanding of the reality of the organizations is looked to arrive á, analyzing the scene of the technology and information and its paper in way the construction of the organizational culture, having for base the relevance that both possess for the process of the dissemination of the values of the Social Responsibility for its incorporation in the internal public of the organizations.

Nas últimas décadas a tecnologia tem sido incorporada à realidade de maneira a reconfigurar todo o cenário atual, trazendo consigo profundas transformações que impactam em todos os campos do conhecimento humano e sobremaneira no comportamento social. Na informação os impactos têm sido diretos, levando em consideração a concomitância do processo de tecnologia à explosão informacional e sua aplicabilidade no ambiente organizacional. Nesse sentido, surge como problema o impacto que a tecnologia aliada à informação tem sobre a construção de valores sociais da cultura de uma organização. Este trabalho busca compreender a maneira como a tecnologia e a informação vem trabalhando na sua disseminação e, desta maneira, construir os valores que são discursados pelas organizações socialmente responsáveis, diante da realidade do novo contexto da revolução das TIC's - Tecnologias da Informação e Comunicação. O trabalho segue como norte eixos de discussão e estudo, sendo: tecnologia - informação - cultura organizacional e responsabilidade social. No intuito de organizar a busca por esse conhecimento, dispõem-se do método comparativo para formar o cenário das organizações socialmente responsáveis, utilizando-se de dois instrumentos de coleta de dados, a entrevista e o questionário. Através dos dados coletados, procura-se chegar á compreensão da realidade das organizações, analisando o cenário da tecnologia e informação e seu papel em meio a construção da cultura organizacional, tendo por base a relevância que ambos possuem para o processo da disseminação dos valores da Responsabilidade Social para sua incorporação no público interno das organizações.
Keywords: Cultura organizacional; Responsabilidade social; Tecnologia da informação; Ciência da informação; Organizational culture; Social responsibility; Information and technology